2008
DOI: 10.1590/s0103-64402008000300014
|View full text |Cite
|
Sign up to set email alerts
|

Academic trajectories of dental researchers receiving CNPq's productivity grants

Abstract: The present study analyzed the profile of dental researchers receiving grants related to their productivity in research from the Brazilian National Research and Development Council (CNPq). Data collection was carried out in March 2008, using the Brazilian database for curriculum vitae (Lattes Format). There were 144 researchers registered in the database and linked to 25 institutions. These researchers published a total of 12,997 full-text articles, 6,927 of which were published in the last 5 years. Category 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 4 publications
1
16
0
16
Order By: Relevance
“…Recently, this field has undergone consider- opment between macro-regions in Brazil, and these discrepancies have also manifested in the distribution of scientific, technological and human resources as well as scientific production. 4 In the present study, a greater proportion of scientific publications was found in the state of São Paulo, which contains seven of the 10 most productive Brazilian universities. Moreover, other states from southeastern and southern regions have experienced a significant increase in scientific research, with specific emphasis on the states of Paraná and Minas Gerais.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Recently, this field has undergone consider- opment between macro-regions in Brazil, and these discrepancies have also manifested in the distribution of scientific, technological and human resources as well as scientific production. 4 In the present study, a greater proportion of scientific publications was found in the state of São Paulo, which contains seven of the 10 most productive Brazilian universities. Moreover, other states from southeastern and southern regions have experienced a significant increase in scientific research, with specific emphasis on the states of Paraná and Minas Gerais.…”
Section: Discussionsupporting
confidence: 40%
“…3 Moreover, there has been an increase in the number of references to Brazilian dental stud-ies indexed in international databases (ISI Web of Science). 4 This fact is of considerable importance, as scientific production establishes a link between dental students and professionals, thereby uniting the national perspective of Brazilian dentistry. 5 Brazilian dental research is currently one of the most respected areas of dental research in the international scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…The profile and the scientific production of research productivity fellows in various areas of knowledge, including communication science [11], medicine [2,7,6,9], chemistry [8], and zoology [10], have been investigated in the last years. However, as far as we know, there is no study concerning the profile and the production of PQ fellows in the field of mathematics (including applied mathematics).…”
Section: Introductionmentioning
confidence: 99%
“…Outra possível estratégia seria a montagem de redes de colaboração que aproveitassem a gama de bolsistas já alocadas em outras regiões em projetos conjuntos. Tais desequilíbrios regionais não são exclusividade da área de Veterinária e já foram relatados em outras áreas do conhecimento (Oliveira et al 2012;Scarpelli et al 2008). …”
Section: Distribuição Geográficaunclassified
“…Deste modo, sendo o grupo de Bolsistas de Produtividade um conjunto de indivíduos que deve ter por concepção um nível de produção formação de recursos humano e impacto científico elevado, os estudos que busquem esmiuçar as características deste grupo de modo a traçar um perfil destes indivíduos se tornam de interesse de toda a comunidade científica nacional. Independentemente da área de atuação, uma série de estudos vem sendo realizada neste sentido nos últimos anos (Barata & Goldbaum 2003, Cavalcante et al 2008, Lino et al 2010, Martelli-Junior et al 2010, Oliveira et al 2012, Oliveira et al 2011, Santos et al 2010, Scarpelli et al 2008, Toffoli & Ferreira 2011.…”
Section: Introductionunclassified